ISLAM SEBAGAI SISTEM BUDAYA, REALITAS DAN KEBERAGAMAN PERSPEKTIF BASSAM TIBI - Kurniawan Kurniawan (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2021)
In essence, religion has a function that is closely related to people's life. It is undeniable that the combination of religion and culture forms a binding bond. In culture, it contains ideas in humans so that they form symbols in religion. This raises a social reality in the aspect of plurality in religious communities. This research examines how to understand Islam as a cultural system so that it raises social facts in the lives of various people who believe in Bassam Tibi's perspective of religion. Bassam Tibi offers a pattern of plurality in understanding the religion of culture in the form of symbolic understanding of social facts, Islam as a cultural system is able to respect religions other than Islam. This research study is in the form of research that comes from a variety of literature that discusses Islam as a cultural system, social reality, and plurality. The findings show that the politicization of religion is a social fact that produces religious fundamentalism. Fundamentalism often creates clashes in Islam and problems in political ideology in the world.